A Functional Variant in MicroRNA-196a2 Is Associated with Susceptibility of Colorectal Cancer in a Chinese Population - Zhan, Jun-fang; Chen, Long-hua; Chen, Zhi-xian; Yuan, Ya-wei; Xie, Guo-zhu; Sun, Ai-min; Liu, Ying (Archives of medical research, 2011)
MicroRNAs (miRNA) can act as oncogenes or tumor suppressors. Polymorphisms present in pri-, pre- and mature miRNAs can potentially modulate the expression of hundreds of genes, broadly affecting miRNA function. Notably, the rs11614913 SNP in miR-196a2 has been implicated in carcinogenesis, but its association with colorectal cancer (CRC) remains unexplored. We performed a case−control study to investigate the genetic association between this functional SNP and CRC susceptibility and progression. We genotyped the rs11614913 SNP in 252 CRC patients and 543 healthy controls by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP). In addition, we examined miR-196a expression level in colorectal cancer tissues ( n = 50) obtained from the studied CRC patients. Frequency of the CC genotype was higher in CRC patients than controls, implying that the subjects with the CC genotype or C allele containing genotypes (CT and CC) have a higher risk of CRC. However, no significant association between this polymorphism and CRC progression was observed. Expression analysis revealed that rs11614913 CC or carrying at least one C allele was associated with a significantly increased level of mature miR-196a ( p = 0.010 or = 0.022). The present study provides the first evidence that miR-196a2 polymorphism may contribute to CRC susceptibility in a Chinese population through modulating mature miR-196a expression.